2007
DOI: 10.1016/j.molcel.2006.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Mechanism of mRNA Capping by the RNA-Dependent RNA Polymerase of Vesicular Stomatitis Virus

Abstract: All known eukaryotic and some viral mRNA capping enzymes (CEs) transfer a GMP moiety of GTP to the 5'-diphosphate end of the acceptor RNA via a covalent enzyme-GMP intermediate to generate the cap structure. In striking contrast, the putative CE of vesicular stomatitis virus (VSV), a prototype of nonsegmented negative-strand (NNS) RNA viruses including rabies, measles, and Ebola, incorporates the GDP moiety of GTP into the cap structure of transcribing mRNAs. Here, we report that the RNA-dependent RNA polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
322
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(339 citation statements)
references
References 53 publications
11
322
1
5
Order By: Relevance
“…However, in non-segmented negative-sense RNA viruses, GT activity has only been demonstrated for VSV L protein (Ogino & Banerjee, 2007). In the present work, we have demonstrated, for the first time for any paramyxovirus, that L protein is able to cap viral mRNA.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…However, in non-segmented negative-sense RNA viruses, GT activity has only been demonstrated for VSV L protein (Ogino & Banerjee, 2007). In the present work, we have demonstrated, for the first time for any paramyxovirus, that L protein is able to cap viral mRNA.…”
Section: Discussionmentioning
confidence: 62%
“…RTPase activity of L protein, the first step in viral mRNA capping, was tested in vitro using synthetic c-32 P-labelled RNA substrate containing sequences corresponding to viral genes. Viral mRNA 59 cis sequences were used as the substrate because in many negative-sense RNA viruses, the capping machinery of these viruses requires specific cis-acting signals in the RNA (Ogino et al, 2005;Ogino & Banerjee, 2007;Wang et al, 2007). Under optimal conditions, L protein in the RNP complex, as well as L protein co-expressed with P protein in insect cells, efficiently catalyses the removal of cphosphate from the triphosphate-ended RNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In direct contrast, we have recently shown that the multifunctional RNA-dependent RNA polymerase (RdRp) L protein (2,109 amino acids) of vesicular stomatitis virus (VSV), a prototype nonsegmented negative-strand (NNS) RNA virus belonging to the genus Vesiculovirus of the family Rhabdoviridae in the order Mononegavirales, carries out an unconventional mRNA capping mechanism that involves stepwise action of guanosine 5′-triphosphatase (GTPase) followed by RNA:GDP polyribonucleotidyltransferase (PRNTase) (4,5), as proposed below:…”
mentioning
confidence: 99%